Bioinductive and anti-inflammatory properties of Propolis and Biodentine on SHED - Yogesh Kale; Swapnil Yadav; Mahesh Dadpe; Prasanna Dahake; Shrikant Kendre (Saudi Dental Journal)
Objectives: This study aimed to evaluate and compare the cell viability, differentiation potential and anti-inflammatory potential of propolis and Biodentine™ on stem cells isolated from human exfoliated deciduous teeth (SHED). Materials and methods: SHED were segregated and cultured from the dental pulp of children after therapeutic extraction. Microculture Tetrazolium Assay (MTT) assay was carried out for assessing cell proliferation potential of propolis and Biodentine at different concentrations. As per the results from cell proliferation assay, cell differentiation potential of SHED was evaluated at concentration of 12.5 μg/ml using Alizarin Red staining. The anti-inflammatory potential of test materials was evaluated using gelatin zymography by detecting MMP-2 and MMP-9. Results: The maximum cell proliferation percentage of SHED treated with propolis and Biodentine was observed at a concentration of 12.5 μg/ml, on day 7, 14 and 21 with Biodentine having maximum cell proliferation potential followed by propolis. SHED treated with Biodentine showed maximum cell differentiation on day 7 (107.16), 14 (106.29) and 21 (107.72). However, anti-inflammatory activity against MMP-2 was 95 % with propolis and 85 % with Biodentine and whereas, against MMP-9 it was 65 % for propolis and 47 % for Biodentine. Conclusion: Propolis shows comparable cell viability, cell proliferation and differentiation potential on SHED when compared to Biodentine. It also exhibits better invitro anti-inflammatory activity on SHED compared to Biodentine. Further studies are warranted to validate the application of propolis as an effective and economical alternative biocompatible agent to Biodentine for vital pulp therapies.